Case report: Spinal drop metastasis of IDH-mutant, 1p/19q-codeleted oligodendroglioma - Karaman, Ahmet Kursat; Korkmazer, Bora; Urganci, Nil; Baş, Gülçin; Arslan, Serdar; Comunoglu, Nil; Hanci, Mehmet Murat; Kızılkılıç, Osman (Frontiers in Neurology, 2022)
Background: Symptomatic spinal metastases of oligodendroglioma are rare. Moreover, none of the previously published cases demonstrated the typical IDH mutation and 1p/19q-codeletion for this glial tumor. This case presents an IDH mutant, 1p/19q-codeleted oligodendroglioma with multiple spinal drop metastases. Case description: We report a case of a 55-year-old woman with left frontal grade 3 oligodendroglioma diagnosed 3 years ago. No tumor recurrence was observed in post-operative follow-up MRI examinations. However, she was admitted to our institution again with severe low back pain. Gadolinium enhanced MRI of the spine revealed an intradural, extramedullary metastatic lesion between T11-L1 levels and multiple enhancing metastatic tumor deposits around cauda equine roots between L4-S1. T11-T12 midline laminectomy was performed and gross total resection of metastatic lesions was achieved. Final histological diagnosis of the spinal lesions was WHO Grade 3 Oligodendroglioma, IDH-mutant, 1p/19q-codeleted. Conclusion: This case is the first molecularly-defined spinal metastatic oligodendroglioma. The possibility of drop metastasis should be kept in mind in oligodendroglioma patients with spinal cord-related symptoms. There is no standard approach for the diagnosis and treatment of spinal metastases of this type of glial tumor.